Implementation of the Inclusion Style Method to Improve Learning Outcomes in the Game of Basketball for Class IV Students at SDN Mojoroto 02 Kediri City in 2024/2025 - Iva Alivatul Kartika Sari; Nur Ahmad Muharram; Rafli Qaulan Kurniawan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This Classroom Action Research is motivated by the importance of learning as the core of the educational process. In its implementation, teachers face challenges in the form of differences in learning abilities among students, which causes some students to have difficulty in understanding the material. The inclusive style method in Physical Education, Sports, and Health learning aims to provide the same assignments with varying levels of difficulty. In this method, teachers set learning tasks with different difficulty criteria, while students are given the freedom to choose assignments that suit their abilities. This study aims to determine the improvement in learning outcomes in basketball games through the application of the inclusive style method in grade VI Semester 1 students at SDN Mojoroto 02 Kediri City in the 2024/2025 academic year. The results of the study showed an increase in student learning outcomes, with an average score increasing from 71.34 in the pre-cycle to 74.72 in cycle I, and 77.94 in cycle II. In addition, the level of learning completion also increased, namely from 51.15% in the pre-cycle to 75% (25 students) in cycle I, and increased again to 90.62% (29 students) in cycle II. The conclusion of this study is that the application of the inclusion style method is effective in improving learning outcomes in basketball games. Therefore, it is recommended that teachers continue to innovate in learning so that students are more motivated and do not feel bored, especially in the subjects of Physical Education, Sports, and Health.